Analysis of EEG Patterns in Subjects with Panic Attacks - Dick, O. E.; Svyatogor, I. A.; Reznikova, T. N.; Fedoryaka, D. A.; Nozdrachev, A. D. (Human physiology, 2020)
The dynamics of the photic driving reaction was studied in subjects with panic attacks, using wavelet and recurrence analyses of electroencephalographic (EEG) patterns. Quantitative measures of the driving reaction to the given frequency were estimated from the increase in the energy of the wavelet spectrum during photostimulation, the coefficient of photic driving, and parameters of a joint recurrence plot of the light stimulus and EEG pattern (the rate and time of recurrence of the EEG trajectory into the vicinity of a previous point). The parameters were determined before and after non-drug therapy, which included activation and training of artificial stable functional connections (ASFCs) in the brain. The formation of ASFCs was found to decrease both asymmetry in occipital lobe responses to the photostimulus and the degree of neuroticism in subjects with panic attacks. The changes were reflected in decreasing values of the photic driving coefficient and recurrence rate and increasing values of the recurrence time. The improvement of the subject’s psychophysiological state after a course of ASFC activation was confirmed by a positive dynamics of psychophysiological testing data.